The evolution of Value-at-Risk disclosure: A study of fifteen European banks between 2004 and 2011. - HILLION, Loic (2012)
This research is an empirical investigation on the Value at Risk disclosures of European banks between 2004 and 2011. It is based on the annual reports of fifteen banks during an eight years period. In a first time, it is using a content analysis to build a risk disclosure index, reflecting both the qualitative and the quantitative aspects of the annual report. This index is used to assess the evolution of VaR disclosures through time and illustrates the differences between Euro currency users and European countries using their own currency. This study is also utilizing this index as a dependent variable for a multiple regression analysis, which is performed to assess the relationship between the size, profitability, firm’s level of risk, zone effect and the dependent variable index. A positive relationship was found for the size and the zone effect. On the other hand, a negative relationship was found for the profitability and an insignificant relationship with the level of risk.